Pengaruh Motivasi Belajar Dan Kepercayaan Diri Terhadap Penguasaan Konsep Pada Pembelajaran Matematika Di SD Swasta Jaktim - Veronica Ari Nugroho Rini; Laurens Kaluge (Journal on Education, 2024)
Mathematics lessons playing important roles in problem-solving skills. Problem-solving skills can be measured from students' mastery of concepts which is the result of learning activities to understand objects through observation and experience. This research aimed to prove the influence of using the Magic Cards educational game media, learning motivation, self-confidence, and the interaction between learning motivation and self-confidence on mastery of concepts in Mathematics. Data collection was carried out by using written tests and questionnaires. The cluster random sampling was used to obtain the research subjects. The samples of this study were two learning groups consisted of 61 grade II primary pupils in VLD, East Jakarta. This study applied two sorts of design, namely experimental and correlational with a quantitative approach. The data analysis in this research is descriptive and inferential - using multiple linear regression. The results of the study showed that the use of the Magic Cards as an educational game media had positive effects on concept mastery. Learning motivation and self-confidence also had positive effects on concept mastery. However, no interaction effects between learning motivation and self-confidence on concept mastery in Mathematics learning for grade II pupils of private primary schools in East Jakarta.